2015 CHESS Users' Meeting and Workshops. Issue 1 (2nd January 2016) - Ko, Peter; Finkelstein, Ken; Lukk, Tiit
Abstract : The annual users' meeting and workshops at Cornell High Energy Synchrotron Source (CHESS) were held from June 9 to 10, 2015, attracting 175 attendees to Ithaca, NY.